Amenorrhea after lung cancer treatment. Issue 3 (March 2019) - Cathcart-Rake, Elizabeth J.; Ruddy, Kathryn J.; Gupta, Ruchi; Kremers, Walter; Gast, Kelly; Su, H. Irene; Partridge, Ann H.; Stewart, Elizabeth A.; Liu, Han; He, Yanqi; Yang, Ping
Abstract: Objective: More than 5, 000 premenopausal women are diagnosed with lung cancer annually in the United States. Limited data exist regarding the risk of treatment-related amenorrhea, a surrogate for infertility and early menopause, after systemic therapies for lung cancer. Methods: Premenopausal women diagnosed with lung cancer under age 50 were surveyed at diagnosis and annually thereafter about their menstrual status as a part of the Mayo Clinic Epidemiology and Genetics of Lung Cancer Research Program. Types of lung cancer-directed treatments were recorded, and frequencies of self-reported menopause at each survey were calculated. Results: A cohort of 182 premenopausal women were included in this study, with average age at lung cancer diagnosis 43 years (SD 6). Among the 85 patients who received chemotherapy, 64% self-reported that they had become menopausal within a year of diagnosis. Platinum salts were universally included in these chemotherapy regimens, and the majority of these women also received taxanes within 1 year of diagnosis. Only 15% of the 94 patients who did not receive systemic therapy within 1 year of diagnosis experienced self-reported menopause. Three patients received targeted therapy alone, two of whom remained premenopausal at the final qualifying survey, completed a median of 3 years after diagnosis. Conclusions: Chemotherapy for lung cancer patients appears to increase risk of early loss of menses in survivors.